Impact of intermediate sites on bulk diffusion barriers: Mg intercalation in Mg2Mo3O8. Issue 45 (4th November 2016) - Gautam, Gopalakrishnan Sai; Sun, Xiaoqi; Duffort, Victor; Nazar, Linda F.; Ceder, Gerbrand
Abstract : An experimental and theoretical evaluation of mobility bottlenecks in Mg2 Mo3 O8, a potential Mg battery cathode material. Abstract : The ongoing search for high voltage positive electrode materials for Mg batteries has been primarily hampered by poor Mg mobility in bulk oxide frameworks. Motivated by the presence of Mo3 clusters that can facilitate charge redistribution and the presence of Mg in a non-preferred (tetrahedral) coordination environment, we have investigated the Mg (de)intercalation behavior in layered-Mg2 Mo3 O8, a potential positive electrode. While no electrochemical activity is observed, chemical demagnesiation of Mg2 Mo3 O8 is successful but leads to amorphization. Subsequent first-principles calculations predict a strong thermodynamic driving force for structure decomposition at low Mg concentrations and high activation barriers for bulk Mg diffusion, in agreement with experimental observations. Further analysis of the Mg diffusion pathway reveals an O–Mg–O dumbbell intermediate site that creates a high Mg 2+ migration barrier, indicating the influence of transition states on setting the magnitude of migration barriers.